2009
DOI: 10.1021/la901189k
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the Viscosity Peak in Wormlike Micellar Solutions. 1. Mixed Catanionic Surfactants. A Cryo-Transmission Electron Microscopy Study

Abstract: The rheology of wormlike micelles ("worms") formed by surfactants in water often follows nonmonotonic trends as functions of composition. For example, a study by Raghavan et al. (Langmuir 2002, 18, 3797) on mixtures of the anionic surfactant sodium oleate (NaOA) and the cationic surfactant octyl trimethylammonium bromide (OTAB) reported a pronounced peak in the zero-shear viscosity eta0 as a function of NaOA/OTAB ratio at a constant surfactant concentration (3 wt %). In this work, we study the origins of rheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 41 publications
11
103
0
Order By: Relevance
“…An example hydrotrope is sodium benzoate, which may be considered as a "primitive" short chain surfactant. The presence of a bulky hydrotrope is recognised as being critical for micellar elongation, with these systems shown to produce substantial increases in solution viscosities [10]. Close investigation by NMR and computer simulations revealed that the hydrotrope counterions adsorb at the micellar interfacial region [11].…”
Section: Introductionmentioning
confidence: 99%
“…An example hydrotrope is sodium benzoate, which may be considered as a "primitive" short chain surfactant. The presence of a bulky hydrotrope is recognised as being critical for micellar elongation, with these systems shown to produce substantial increases in solution viscosities [10]. Close investigation by NMR and computer simulations revealed that the hydrotrope counterions adsorb at the micellar interfacial region [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in mixed anionic / cationic surfactant systems it may also be due to the shortening of micellar chains as was demonstrated for sodium oleate / C 8 TAB micelles by cryo-transmission electron microscopy [22]. But one should note that the experiments in the last paper [22] were performed at constant total concentration of cationic and anionic surfactants and therefore the amount of long-chain anionic surfactant was decreased as the cationic short-chain surfactant was added, which may favor a decrease of micellar length. In contrast, in the present paper, we keep the anionic surfactant concentration constant.…”
Section: Resultsmentioning
confidence: 91%
“…NOESY experiments disclose that 1-hexanol resides close to palisade layer and below the head group inside CTAT micelles. Doping with 1-hexanol offers a simple and easy method of controlling the size and shape of CTAT micelles from worm-like to vesicles that nd many industrial applications as well as applications in personal and home care products and in templated synthesis of mesoporous materials 42,[79][80][81] and can also be utilized for micellar-enhanced ultraltration process.…”
Section: Discussionmentioning
confidence: 99%